2007
DOI: 10.1172/jci30117
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor–2 (HIF-2) regulates hepatic erythropoietin in vivo

Abstract: Erythropoiesis is critically dependent on erythropoietin (EPO), a glycoprotein hormone that is regulated by hypoxia-inducible factor (HIF). Hepatocytes are the primary source of extrarenal EPO in the adult and express HIF-1 and HIF-2, whose roles in the hypoxic induction of EPO remain controversial. In order to define the role of HIF-1 and HIF-2 in the regulation of hepatic EPO expression, we have generated mice with conditional inactivation of Hif-1α and/or Hif-2α (Epas1) in hepatocytes. We have previously sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
436
6
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(481 citation statements)
references
References 72 publications
30
436
6
9
Order By: Relevance
“…Conditional knockout of HIF-2α after birth demonstrated that HIF-2α plays a critical role in adult erythropoiesis [13]. In addition, studies using mice with conditional knockout of HIF-1α and/or HIF-2α in hepatocytes revealed that the hypoxic induction of liver EPO in anemic mice was also HIF-2α dependent [14].…”
Section: Mechanisms Of Renal Erythropoietin Productionmentioning
confidence: 99%
“…Conditional knockout of HIF-2α after birth demonstrated that HIF-2α plays a critical role in adult erythropoiesis [13]. In addition, studies using mice with conditional knockout of HIF-1α and/or HIF-2α in hepatocytes revealed that the hypoxic induction of liver EPO in anemic mice was also HIF-2α dependent [14].…”
Section: Mechanisms Of Renal Erythropoietin Productionmentioning
confidence: 99%
“…In addition, Hif2a -/-mice display defects in hematopoietic development due to greatly reduced EPO levels in the kidney (Scortegagna et al 2003;Scortegagna et al 2005;Rankin et al 2007). Administration of exogenous EPO reverts this phenotype as well as some of the other defects associated with Hif2a elimination (Scortegagna et al 2005).…”
Section: Phenotypic Effects Of Hif-2α Eliminationmentioning
confidence: 99%
“…Renal cysts at low frequency; inactivation of ARNT, but not HIF-1a suppressed the development of renal cysts Liver Haase et al 76 Rankin et al 31 Rankin et al 32 …”
Section: Proximal Renal Tubulementioning
confidence: 99%
“…For example, genes encoding glycolytic enzymes appear to be predominantly controlled by HIF-1, 29 whereas HIF-2 appears to be the main regulator of VEGF and EPO in tissues that express both HIF-1 and HIF-2. [30][31][32][33] Target gene preference may be the result of tissue-specific interactions with other nuclear factors, differential interactions with transcriptional cofactors or a reflection of tissue-and celltype-dependent differences in the ratios of HIF-a protein levels (for a review on this topic see Wenger et al 28 ).…”
mentioning
confidence: 99%